CMedBench: A Comprehensive Benchmark for Efficient Medical Large Language Models - Gao, Shengbo; Guo, Jinyang; Su, Lixian; Ding, Yifu; Gu, Shiqiao; Liu, Aishan; Ma, Yuqing; Zhang, Zhiwang; Liu, Xianglong (Proceedings of the AAAI Conference on Artificial Intelligence, 2026)
Large Language Models (LLMs) hold significant potential for enhancing healthcare applications, yet their deployment is hindered by high computational and memory demands. Model compression techniques offer solutions to reduce these demands, but their impact on medical LLMs remains underexplored. In this paper, we introduce CMedBench, the first comprehensive benchmark for evaluating compressed LLMs in medical contexts. CMedBench assesses five core dimensions: Medical Knowledge Ability, Medical Application Ability, Trustworthiness Maintenance, Compression Cross Combination, and Computational Efficiency. Through extensive empirical studies, we analyze the trade-offs between model efficiency and clinical performance across diverse models, datasets, and compression strategies. Our findings highlight critical limitations in current evaluation practices and provide a robust framework for aligning compression strategies with medical requirements. CMedBench serves as a vital resource for researchers and practitioners, guiding the development of efficient, trustworthy, and clinically effective LLMs for healthcare applications.